20. DETERMINATION OF THE ANTIFUNGAL DRUG SUSCEPTIBILITY OF CANDIDA SPP. ISOLATED FROM SKIN AND MUCOUS MEMBRANES OF PATIENTS TREATED AT QUYHOA NATIONAL LEPROSY DERMATOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objectives: Candida spp, which causes skin and mucous membrane infection, is resistant to manyantifungal drugs. This study was conducted to determine the sensitivity of Candida spp in patientstreated at Quy Hoa National Leprosy Dermatology Hospital to find the most effective antifungaldrugs.Study subjects and methods: The study was conducted in the laboratory with a descriptive researchdesign.Results: C. albicans was sensitive to Amphotericin B, Econazole and Nystatin at high rates of73.33%, 73.33% and 60.00%, respectively. C. tropicalis was susceptible to Amphotericin B at therate of 75.00%, and resistant to 5-fluorocytosine, Ketoconazole and Miconazole at the resistancerate of 75.0%, 50.0%. C. glabrata was sensitive to many Miconazole-based antifungal drugs at100%, to Amphotericin B at 75%, and to Fluconazole and Nystatin, but resistant to Ketoconazole,5-fluorocytosine and Itraconazole at 50%. C. parapsilosis was susceptible to many antifungal drugssuch as Clotrimazole, Itraconazole, Fluconazole, Nystatin and Amphotericin B at the rates of 100%.C. parapsilosis was resistant to 5-fluorocytosine and Miconazole at 50.0%.Conclusions: Most of the Candida spp, such as C. albicans, C. tropicalis, C. glabrata, C. glabratawere susceptible to Amphotericin B with susceptibility rates ranging from 75.0% to 100.0%.
Keywords: Fungi, Candida spp; sensitive, resistant.